Acontece que são baianos: das fotorreportagens de Pierre Verger ao desenho das páginas na revista O Cruzeiro, traçando os sentidos - Paixão, Ronaldo dos Santos da (2015)
Acontece que são baianos: from the photoreports of Pierre Verger to the Design in the pages of the O Cruzeiro magazine, outlining senses is the result of a study on Design and page design, specifically the layout in the graphic space of the O Cruzeiro magazine. The study investigates how Design as a layout produces meaning in the two pages space of the five photoreports of Pierre Verger entitled Acontece que são baianos, published in the August 1951 editions. Photoreports showing the daily life and cultural practices of the former slave descendants who lived in Brazil during and after the Colonial system and returned to the West Coast of Africa, in Nigeria and Benin. Among some of these cultural practices present in religious and profane celebrations of Catholicism related devotion to the Lord of Bonfim are dance, the songs, cooking, which according to the contents of visual and verbal texts represent the Bahian culture. Through texts written by Gilberto Freyre and the photoreport of Pierre Verger sought to discuss the perspective approach of Culture at that time about Bahia and the West Coast of Africa. Through the photoreport analyzes Design as layout in the graphic design of the magazine, and the construction of meaning from the three lines of analysis: the first suggested by Nadja Peregrino which made a pioneering study on the magazine and the page composition through the photoreport; the second related to the visual techniques applied to Design in the Donis A. Dondis conception and finally the analysis through the elements of Design approached by Wucius Wong.